Effect of intercritical annealing on the mechanical properties of dual-phase steel. (14th September 2022) - Ayres, James; Penney, David; Evans, Peter; Underhill, Richard
ABSTRACT: A dual-phase steel chemistry has been processed with varying intercritical annealing temperatures and the properties investigated. It was found that increasing the temperature in the intercritical region led to an increase in the volume fraction (52%–65%) and grain size (1.8–3.3 µm) of martensite whilst the volume fraction and grain size of ferrite decreased. The highest tensile strengths were found at low intercritical temperatures, achieving 935 MPa whilst the highest elongation values of 21% were achieved at the highest intercritical temperatures.